2014
DOI: 10.1371/journal.pone.0084663
|View full text |Cite
|
Sign up to set email alerts
|

4-Phenylbutyrate Inhibits Tunicamycin-Induced Acute Kidney Injury via CHOP/GADD153 Repression

Abstract: Different forms of acute kidney injury (AKI) have been associated with endoplasmic reticulum (ER) stress; these include AKI caused by acetaminophen, antibiotics, cisplatin, and radiocontrast. Tunicamycin (TM) is a nucleoside antibiotic known to induce ER stress and is a commonly used inducer of AKI. 4-phenylbutyrate (4-PBA) is an FDA approved substance used in children who suffer from urea cycle disorders. 4-PBA acts as an ER stress inhibitor by aiding in protein folding at the molecular level and preventing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 38 publications
8
71
0
Order By: Relevance
“…Values were normalized using β-actin and expressed as percentage of DMSO-treated control for GRP78 or percentage of TM-treated group for CHOP (mean ± SEM; n = 3) protects against TM-induced expression of both GRP78 and CHOP. However, a higher magnitude of reduction was observed on CHOP expression (Carlisle et al 2014). Our findings are in line with a previous study in HK-2 cells by Carlisle et al, where 4PBA has been shown to prevent TM-induced CHOP expression without affecting the expression of GRP78 (Carlisle et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Values were normalized using β-actin and expressed as percentage of DMSO-treated control for GRP78 or percentage of TM-treated group for CHOP (mean ± SEM; n = 3) protects against TM-induced expression of both GRP78 and CHOP. However, a higher magnitude of reduction was observed on CHOP expression (Carlisle et al 2014). Our findings are in line with a previous study in HK-2 cells by Carlisle et al, where 4PBA has been shown to prevent TM-induced CHOP expression without affecting the expression of GRP78 (Carlisle et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…We compared the potency and efficacy of piperine and its analogs against 4-phenylbutyrate (4PBA), a well-known chemical chaperone, used at 1 and 2 mM concentrations (Carlisle et al 2014) (Fig. 2a-d).…”
Section: Synthesis and Characterization Of Amide-substituted Piperinementioning
confidence: 99%
“…2008; Carlisle et al. 2014). Notably, tunicamycin‐induced acute kidney injury is blunted in CHOP knockout mice, or in mice treated with the chemical chaperone 4‐PBA (Marciniak et al.…”
Section: Introductionmentioning
confidence: 99%
“…2004; Carlisle et al. 2014). In liver, the lesions observed in tunicamycin‐intoxicated animals include steatosis, bile ductular hyperplasia, swollen hepatocytes, and the presence of apoptotic bodies (Finnie and O'Shea 1989; Finnie and O'Shea 1990b; Finnie et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 4-PBA can suppress ER stress. 21, 22 Ozcan et al 20 found that both UDCA and 4-PBA alleviated ER stress, which resulted in the normalization of hyperglycemia and restoration of systemic insulin sensitivity, thereby revealing their potential benefits in the treatment of type 2 diabetes. Therefore, we hypothesize that UDCA and 4-PBA may prevent kidney damage in type 2 diabetic mellitus through the inhibition of ER stress.…”
mentioning
confidence: 99%